The new democratisation: social media impact on the political process in Sub-Saharan Africa - Ajaegbu, Oguchi Onyeizu; Ajaegbu, Chigozirim (Frontiers in Communication, 2024)
The integration of social media into political discourse is becoming the norm, facilitating citizen engagement and amplifying voices across the Sub-Saharan Africa (SSA). This study centred on a literature review on the role of social media in political participation within the region. Through exploration across three databases, 50 articles were identified, with 42% of these closely related to the research focus and categorized under five distinct themes. Findings reveal various perspectives on the impact of social media on political engagement, with scholars offering different interpretations on its influence. Furthermore, majority of research underscores the role of social media in mobilizing protests and revolutionary movements driven by heightened participation observed in some SSA countries. Social media platforms are increasingly perceived as avenues to express opinions on pertinent issues contesting unfavourable government actions. Thus, this study posits the emergence of a "New Democratisation in Sub-Saharan Africa", propelled by the positive utilization of social media in political spheres.